UJI DAYA HAMBAT EKSTRAK ETANOL RIMPANG TEMU GIRING (CURCUMA HEY NEANA VAL.) TERHADAP PERTUMBUHAN ESCHERICHIA COLI SECARA IN VITRO - Aditya Maulana Perdana Putra; Rustifah Rustifah; Muhammad Arsyad (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Infection is a major problem that the world’s attention. Infectious diseases have caused the death of over 13 million people worldwide every year, particularly in the developing countries such as Indonesia. One of the species of bacteria that cause infections are Escherichia coli. Curcuma heyneana rhizome (Curcuma heyneana Val.) is a plant that is often used as a traditional medicine to antibacterial. This study was intended to determine the antibacterial inhibition activity, and minimum inhibitory concentrations (MIC) from the usage of an ethanol extract in the curcuma heyneana rhizome (Curcuma heyneana Val.) for the growth of an Escherchia coli by in vitro.Curcuma heyneana rhizome (Curcuma heyneana Val.) was extracted using maseration method with solvent ethanol. Each extracts identified the active compounds group consisting of flavonoids, saponins, curcumin, volatile oil, and tannins. This study was an experimental laboratoric by using the diffusion method with discs blank with 10 treatment groups concentration which are 100%, 50%, 25%, 12,5%, 6,25%, 3,12%, 1,56%, 0,78%, positive control and negative control with three repetitions.The phytochemical screenings analysis showed curcuma heyneana rhizome (Curcuma heyneana Val.) of ethanol extract containing flavonoids, saponins, curcumin, volatile oil, and tannins. Ethanol extract in the curcuma heyneana rhizome (Curcuma heyneana Val.) had an effectiveness in inhibiting the growth of an Escherchia coli by in vitro. Minimum inhibitory concentrations (MIC) from the usage of an ethanol extract in the curcuma heyneana rhizome (Curcuma heyneana Val.) for the growth of an Escherchia coli by in vitro is 12,5% with average inhibition zone 9,77 mm. The results showed that the ethanol extract curcuma heyneana rhizome (Curcuma heyneana Val.) had an effectiveness in inhibiting the growth of an Escherchia coli, it showed inhibition zone diameter due to higher concentrations of the resistance is increasing. Analysis of the test data with Kruskal-Wallis (sig) = 0,001 which is smaller than α < 0,05. It means that there are significant differences in the average diameter of an each concentration of ethanol extract of curcuma heyneana rhizome in i